Faktor-faktor yang Mempengaruhi Pertumbuhan Industri Tempe Skala Rumah Tangga (studi kasus di Kecamatan Semarang Barat dan Semarang Timur) - Sukirman, - (Jurnal Sosial Budaya, 2011)
In line with the progress achieved in the industrial sector at national and regional level, the development of smallÂ  industriesÂ  in the city ofÂ  SemarangÂ  has undergoneÂ  a quiteÂ  satisfactory progress.Â  Based on researcherâsÂ  rareÂ  observations in traditional markets in the city of Semarang, there was an increase of the price of tempeh, as theÂ  result of the increase in prices of basic needs. This research tries to explore more on tempeh industry in the city ofÂ  Semarang, to be specific in West and East Districts of Semarang. It will investigate on how small industry sector,Â  tempeh industry, can exist while examining the factors that affect the income from production.The objective of the research is to analyse the influence of capital, labors, labor skills, as well as the capital on theÂ  growth ofÂ  tempeh industry in household scale in the city of Semarang,.The type of research used is quantitative using analitical descriptive approach with cross sectional research design,Â  therefore the result of the research can be identified at the same time. The result of the research gives an explanation on that there is a positive and significant influence between capital,Â  labors and skills on the growth of tempeh industry. In other words, the variation of the growth of tempeh industryÂ  can develop regarding the capital, labors and labor skills owned.